2015
DOI: 10.1007/s11135-014-0158-9
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards Roma people and migrants: a comparison through a Bayesian multidimensional IRT model

Abstract: In the context of social psychological research on relations between cultural defined groups, the main topics of interest include ethnic prejudice, attitudes and stereotypes. In the present study, in order to measure and compare attitudes towards Roma people and migrants and to investigate how these attitudes vary according to individual characteristics, we develop an integrated model which embeds a multidimensional Item Response Theory model for polytomous data into a structural equation formulation. Item and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…For example, Strabac and Listhaug ( 2008 ) found that the percentage of the majority population in Europe objecting to Muslims as neighbors is higher than that objecting to immigrants (in general) as neighbors (Strabac and Listhaug, 2008 ). Fontanella et al ( 2016 , p. 487) suggest that Roma people are the most rejected ethnic group in Europe concluding that “the Roma people continue to be the most discriminated even with respect to migrants and to be classified as a separate reality to which we will not ever get used.”…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Strabac and Listhaug ( 2008 ) found that the percentage of the majority population in Europe objecting to Muslims as neighbors is higher than that objecting to immigrants (in general) as neighbors (Strabac and Listhaug, 2008 ). Fontanella et al ( 2016 , p. 487) suggest that Roma people are the most rejected ethnic group in Europe concluding that “the Roma people continue to be the most discriminated even with respect to migrants and to be classified as a separate reality to which we will not ever get used.”…”
Section: Discussionmentioning
confidence: 99%
“…This approach can be problematic because members of the public may have in mind different types of immigrants when asked to report their views on a general category of immigrants (Blinder, 2015 ). The small and quite recent body of research that distinguishes between groups of immigrants by ethnic or religious origin found that in the European context attitudes toward immigrants vary across groups being more negative toward ethnic minorities (Gorodzeisky and Semyonov, 2009 ; Ford, 2011 ; Ben-Nun Bloom et al, 2015 ); and that opposition is especially pronounced in the case of Muslim (Strabac and Listhaug, 2008 ; Hellwig and Sinno, 2017 ) and Roma out-group populations (Fontanella et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Roma people are sometimes treated with a severe disregard for human rights even in countries with stronger egalitarian norms. For example, Italy has been condemned for relegating Roma people to nomadic camps (European Roma Rights Centre [ERRC], 2000), and a survey revealed the commonness of open, direct, and racist attitudes on the one hand, and dehumanization on the other, even among less prejudiced individuals (Fontanella, Villano, & Di Donato, 2016). Similarly, France has been heavily criticized for collectively criminalizing and deporting Roma people (Castle & Bennhold, 2010).…”
Section: Anti-gypsyism Across Europementioning
confidence: 99%
“…Roma people represent the outsider who is excluded from society. Fontanella, Villano and Di Donato [2015] suggest that this happens especially in the case of those with greater national identity and those who are more likely to show a larger prejudicial predisposition towards Roma people and also migrants. They add that Roma are 'the most discriminated even with respect to migrants' [Fontanella, Villano and Di Donato 2015: 17].…”
Section: Minority Presence As An Explanation Of Far-right Supportmentioning
confidence: 99%